Ultrasonography Findings of Rare Form Deep Vulvar Hemangioma: A Case Report - Purmata, Andrew Theo William Chris; Ubaid, Angling Febriani Ariqoh; Sandy, Emy Noviana; Adiwinoto, Ronald Pratama (Indonesian Journal of Medicine, 2025)
Background: Hemangiomas are the most common vascular tumors in infants and children, they typically appear after birth, grow rapidly, and then gradually involute. Early diagnosis is crucial, but the clinical presentation of hemangiomas can resemble other vascular anomalies, necessitating the use of imaging studies like ultrasonography (US) in order to establish accurate diagnosis. This study aims to present the ultrasonographic characteristics of a rare case of vulvar hemangioma, with the objective of aiding in its differentiation from other vulvar vascular malformations. Case Presentation: A 9-year-old girl presented with a painless vulvar mass that had been enlarging over 3 months. Physical examination revealed a 3 x 2.5 x 1.5 cm, well-defined, skin-colored, non-tender, and immobile mass. Greyscale ultrasonography showed a septated cystic lesion with internal echoes. Doppler ultrasonography showed low flow vascular patterns, suggestive of a hemangioma.  Surgical excision was performed, and histopathology confirmed the diagnosis of a  hemangioma Results: Although vulvar hemangioma is rare, it can mimic other vascular anomalies, making imaging essential for accurate diagnosis and management. Ultrasonography, as a inexpensive and non-invasive imaging modality, plays a crucial role in differentiating hemangiomas from other vascular malformations. Conclusion: Hemangioma is a form of vascular mass and the most common one, at early phase the clinical presentation might resemble other vascular anomalies. Thereby diagnostic modalities such as ultrasonography might be able to help to establish the diagnosis